SENAM AEROBIK INTENSITAS SEDANG DAN PENURUNAN BERAT BADAN, PERSEN LEMAK SERTA RASIO LINGKAR PINGGANG PANGGUL MAHASISWA GIZI YANG OVERWEIGHT - Khusnul Khatimah Khusnul Khatimah Khusnul Khatimah; hikmawaty mas'ud; suriani rauf (Media Gizi Pangan, 2017)
Background: Physical training is one of many method for solving overweight, overgrease and to reach the best freshness of body and fungtional capality from someone.Objectives: Knowing the influence of aerobicnastic (SKJ 2012) in middle intentcity for weight lost, grace percent, and hip waist rim for overweight nutrient student in Health Politeknik of Makassar.Methods: This method is research experiment with one group, pre-test and post-test design. The research will be held in nutrient faculty health polyteknik of Makassar. Sample 30 students of nutrient faculty with overweight status have been choosen by purposive sampling.Results: The result showed that the average of weight loss and grace fat amount was 1,42 kg and 1,96 mm, at the same time, the hip waist rim were not decrease. Based on data analysis found that there were a significant relationship between aerobic with middle intencity and weight loss and grace fat (p=0,000), at the same time,there were not significant relationship between aerobic with middle intentcity and hip waist rim (p=0,882).Conclusions: Energi demand is due to the physical activity. Energy source are drived from the fat-burning in the body. Regular aerobic exercise can reduce the fat strored in body so that weight loss occurs.Keyword : Aerobicnastic, Weight, Grase Persent, Hip Waist Rim